1993
DOI: 10.2307/1939508
|View full text |Cite
|
Sign up to set email alerts
|

Processes Regulating Soil Emissions of NO and N^2O in a Seasonally Dry Tropical Forest

Abstract: While much is known about control of production of NO and N2O by nitrifying and denitrifying bacteria at the cellular level, application of this knowledge to field studies has not yielded unifying concepts that are widely applicable and that foster understanding of global sources of these atmospheric trace gases. We applied a simple conceptual model to the investigation of sources of NO and N2O and the environmental factors affecting fluxes in a drought—deciduous forest of Mexico. Fluxes of NO and N2O were hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
271
3
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 427 publications
(308 citation statements)
references
References 39 publications
(32 reference statements)
31
271
3
3
Order By: Relevance
“…Acetylene inhibition experiments conducted in intact cores taken from this Mexican forest failed to inhibit N20 production in soil cores taken during the wet season with 14% WFPS. Because acetylene inhibits nitrification, failure to inhibit N20 production clearly indicates denitrification is the main process contributing to the production of this trace gas at this site [Davidson et al, 1993]. In our forest soils an increase in heterogeneity of WFPS among soil macrosites can account for denitrification because NO3-produced in one site can move to another site where it is denitrified.…”
Section: Sources Of N20 Emissions From Forest Soils: a Hypothesismentioning
confidence: 83%
See 1 more Smart Citation
“…Acetylene inhibition experiments conducted in intact cores taken from this Mexican forest failed to inhibit N20 production in soil cores taken during the wet season with 14% WFPS. Because acetylene inhibits nitrification, failure to inhibit N20 production clearly indicates denitrification is the main process contributing to the production of this trace gas at this site [Davidson et al, 1993]. In our forest soils an increase in heterogeneity of WFPS among soil macrosites can account for denitrification because NO3-produced in one site can move to another site where it is denitrified.…”
Section: Sources Of N20 Emissions From Forest Soils: a Hypothesismentioning
confidence: 83%
“…Denitrification has been shown to occur even in very dry soils. For example, experiments conducted in a seasonally dry deciduous tropical forest of Mexico [Davidson et at., 1993] demonstrated that even in the very course-textured soil of this forest, where soils moisture content never exceed 20%, denitrification was a modest contributor of N20 emissions. Acetylene inhibition experiments conducted in intact cores taken from this Mexican forest failed to inhibit N20 production in soil cores taken during the wet season with 14% WFPS.…”
Section: Sources Of N20 Emissions From Forest Soils: a Hypothesismentioning
confidence: 99%
“…Von der argued that a drop in the GWT causes a decrease in N 2 O-N production whereas recharge stimulates N 2 O-N production. Recharge can increase groundwater DO, DOC and NO 3 --N resulting in increased N 2 O-N production and could decrease further N 2 O-N reduction (Davidson, et al, 1993). Deurer et al (2008) …”
Section: Indirect N 2 O-n Emissionsmentioning
confidence: 99%
“…Land use change, for example, from natural vegetation to agricultural land, or from grassland to arable land, can strongly impact soil carbon and nutrient concentrations. This is because (1) human activities, such as tillage, harvest and vegetation plantation, could affect soil nutrient decomposition or loss; (2) human disturbance may affect soil moisture by changing micro-climate and plant patterns (Davidson et al, 1993); and (3) species have different nutrient requirements, exploit nutrients with varying efficiency and store or convert nutrients at different rates (Aerts and Chapin, 2000). Changes in land use affect input and output of nutrients and carbon in soils and vegetation.…”
Section: Change Of Soil Nutrients Under Different Land Use Typesmentioning
confidence: 99%